Nutrient Mass Balances and Leaching Losses from a Farmyard Manure Pit in Madhya Pradesh - F. Pax C. Blamey2, Ram C. Dalal2, S.K. Dixit3 and Neal W. Menzies, K. Sammi Reddy, M. Mohanty, D.L.N. Rao Muneshwar Singh, A. Subba Rao, M. (Journal of the Indian Society of Soil Science, 2015)
The quality of farmyard manure (FYM) prepared by farmers by traditional method is poor due to loss of nutrients during its preparation and low nutrient content of inputs. Earlier studies showed that the groundwater collected from habitation areas contained higher concentration of nitrates than those of field areas which was attributed to movement of nutrients from FYM pits to nearby water sources. But little quantitative data exist on nutrient mass balances or their losses via leaching. To address these shortcomings, a study was conducted on a representative, traditional FYM pit in Geelakhedi village, Madhya Pradesh. Cattle dung was the main component of FYM (67%) followed by cattle shed waste (20%); ash, household sweepings, and vegetable waste were minor components. A total of 3700 kg of FYM was produced from the 5760 kg of materials that were put into the pit. Importantly, 39% of the N, 20% of the P and 32% of the K inputs were lost during the preparation of FYM. Nutrients capture on exchange resin cores showed that at least 27% of the N, 30% of the P and 50% of the K were lost through leaching. Further studies are needed to improve accuracy and to determine losses through other mechanisms. Despite nutrient losses, FYM is an important resource that could be even more valuable with reduced nutrient losses.